Chudesnyi vals of Bulat Okudzhava in Polish translations - Kotlarek, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The article is a comparative analysis of three Polish translations of the Russian bard’s (Bulat Okudzhava’s) poem Chudesnyi vals translated by Irena Piotrovska and two different versions by Vitold Voroshilski. The author of this article concentrates on similarities and differences between the original text and its translations, as well as on poem’s musical aspects. The author also investigates how patterns and processes of lexical change determine and affect modification of poetic images and metaphors, concentrating especially on metamorphosis of a man into a plant shown in one of Okudzhava’s poems.